Marketing and promotion of quality by the private sector. The case of Hellas - Dakos V. (Global quality assessment in Mediterranean aquaculture, 2000)
In Hellas a population of over 240 fish farms operating are producing some 45,000 tonnes of sea bream and sea bass. The product of the Hellenic Aquaculture is obliged to compete with some 50,000 tonnes produced in 11 other Mediterranean countries. The period when production was limited and demand exceeded supply has passed, the considerable increase of the tonnage available has turned the market from a seller's market to a buyer's market. The congestion of sellers and high volumes of product to certain markets and specifically to Italy pressed the prices down to almost 50 per cent over the last 5 years with a direct effect on the profitability of the enterprises. The product by its nature deprives the marketers from playing with some elements of the product mix: you cannot create a brand easily or build brand awareness amongst the final consumers, you cannot have special retail packaging, or influence the retail price and so on.
Workshop of the CIHEAM Networks on Technology of Aquaculture in the Mediterranean (TECAM) and Socio-Economic and Legal aspects of Aquaculture in the Mediterranean, 1999/11/29-1999/12/01, Barcelona (Spain)